Analisis Teknik Defamiliarisasi dalam Novel Akar Karya Dewi Lestari - Intan Zuhrotun Nafi’ah; NFN Sugiarti (Madah: Jurnal Bahasa dan Sastra, 2019)
This research aims to reveal (1) technique of defamiliarization in the novel Akar by Dewi Lestari; and (2) the function of defamiliarization. The theory used is formalism of Victor Shklovsky. Close reading is used for method in this research. The data used in this research is the forms of language in the novel. The source of data was obtained from the novel Akar by Dewi Lestari. The result of this research shows that there are three strategies in the novel, namely (1) the utilization of foreign language such as English, Thai, Khmer, and French; (2) the utilization of foreign terms in English and Thai; and (3) the use of Buddhist mantras to purify oneself and Buddhist mantras used when feeling marginalized. The defamilarization function in Akar novel is to add aesthetic value and to make readers more interested in reading.